Agentive (para)synthetic compounds in Russian: a quantitative study of rival constructions - Naccarato, Chiara (Morphology (Dordrecht), 2019)
The paper compares two rival word-formation constructions giving rise to compound agent nouns in Russian, i.e., (para)synthetic compounds formed with the agentive suffixes - ec and - tel’ , such as basnopisec ‘fable writer’ and bytopisatel’ ‘everyday-life writer’. To understand what makes these constructions different from one another, compounds in - ec and - tel’ are analyzed based on a number of formal and semantic criteria, i.e., the part of speech and semantic role of the non-verbal element of the compound, the transitivity and formal aspect of the verbal base of the compound, the animacy of the compound’s referent, and the semantics of the compound. The study is supported by statistical analyses, i.e., conditional inference trees and random forests, which help discriminate the behavior of rival constructions and determine which parameters are more relevant for the comparison. To understand whether diachronic and/or stylistic factors also affect the survival of rival constructions, the data are checked in the Russian National Corpus, which allows retrieving information about the texts in which compounds occur, such as their creation date and textual genre. Finally, the productivity of rival word-formation constructions in modern Russian is discussed both in terms of diachronic changes and in terms of restrictions that the two constructions are subject to. The analyses carried out demonstrate that the two constructions show significant differences regarding their semantics, but also their diachronic and stylistic distribution, as well as their productivity, which prevents one construction from completely ousting the other in modern Russian.